Momentum Concept Learning using Tracker as a Virtual Experiment Model: Looking at Students’ Learning Independence - Subali, Bambang; Ulqia, Nindy; Ellianawati, Ellianawati; Siswanto, Siswanto (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
Visualization of physical phenomena through modeling and virtual experiment help students to understand the physics concepts. The concept of momentum is quite challenging to explain without the help of virtual experiments.This study aimed to analyze students' independent learning after conducting the learning process on the concept of momentum using Tracker software as a virtual experimental model. This study was quasi-experimentalwith the purposive sampling technique to determine the control class and the experimentalclass. There were 42 students involved in this research. The control class was treated by actual experiments on learning, while the experimental class used the Tracker software as a virtual experiment model. The instrument used was questionnaires given at the end of learningto measurestudents’ learning independence. The data were analyzed by using the descriptive statistics method. Learning independence in the control class obtained 51.31% in the medium category, and the experimental class obtained 60.95% in the medium category. Although the average achievement was not significantly different, the aspects of responsibility, motivation, and self-evaluation of the experimental classwere better than that of the control class.